Dr. Mahmood Akhtar: Fueling a Passion for Learning - Ding, Avrilynn; Mansoor, Yasmeen; Aditya, Ishan (The Meducator, 2014)
Dr. Mahmood Akhtar is a researcher in the department of Pediatrics & Medicine at McMaster University. He has a diverse educational background, with a M. Phil. and a Ph.D. in Molecular Microbiology. He has also completed two postdoctoral fellowships at the University of Maryland and McMaster University. Since 2007, Dr. Akhtar has been working with Dr. Mark Tarnopolsky at McMaster University. Aside from his research, he is currently one of the facilitators of the second year Cell Biology course in the Bachelor of Health Sciences (Honours) program.